A Novel Way To Radiolabel Human Butyrylcholinesterase for Positron Emission Tomography through Irreversible Transfer of the Radiolabeled Moiety. (27th June 2016) - Sawatzky, Edgar; Al‐Momani, Ehab; Kobayashi, Ryohei; Higuchi, Takahiro; Samnick, Samuel; Decker, Michael
Abstract: The enzyme butyrylcholinesterase (BChE) is known to be involved in the detoxification of xenobiotics in blood plasma and is associated with the progress of neurodegenerative disorders, diabetes type 2, obesity, and diseases of the cardiovascular system. In the present study, we developed carbamate‐based inhibitors serving as positron emission tomography (PET) radiotracers with 18 F and 11 C as radioisotopes to visualize BChE distribution. These inhibitors are radiolabeled at the carbamate site and transfer this moiety onto BChE, which thus results in covalent and permanent radiolabeling of the enzyme. There are no comparable radiotracers for cholinesterases described to date. By ex vivo autoradiography experiments on mice brain slices and kinetic investigations, selective and covalent transfer of the radiolabeled carbamate moiety onto BChE was proven. These tracers might provide high resolution of BChE distribution in vivo to enable investigations into the pathophysiological mechanisms of diseases associated with alterations in BChE occurrence. Abstract : Irreversible labeling : Carbamate‐based, highly potent, and selective butyrylcholinesterase (BChE) positron emission tomography (PET) radiotracers labeled at the carbamate residue can covalently label human BChE. Such inhibitors might enable mapping of BChE distribution in vivo.